Assessment of complementary feeding knowledge and practices of mothers registered at Anganwadi centers of Jaipur - Nagar, Priyanka; Talikoti, Pooja (International Journal Of Community Medicine And Public Health, 2022)
Background: In children under five, malnutrition is the leading cause of morbidity and mortality. If infants are not correctly fed during their first year of life, they will develop significant health problems and be less productive later in life. Considering the importance of this, the knowledge and practices for these infants were assessed. Methods: The study was carried out in the slum areas of Kachchibasti, Jagatpura, Jaipur among 100 mothers of children aged 6-24 months registered at 10 AWC selected on the basis of average functioning. The knowledge was assessed by using a questionnaire and practices of mothers observed by personal home visits (sample size-20 mothers). Results: Thirty-eight per cent of the mothers were not aware about introduction of complementary feeding. 87% of the mothers are housewives and 94% of mothers are literate. Only 49% of the registered children in age group 6-12 months are collecting the supplementary nutrition, while only 62% are in age group 12-24 months is collecting supplementary nutrition. Conclusions: There is a strong need for timely introduction of complementary foods, nutrition counseling during pregnancy, lactation and illness and making the mothers aware that even the community support is required for the nutrition of the children.